2D BiVO4/g-C3N4 Z-scheme photocatalyst for enhanced overall water splitting - Xie, Hanyi; Zhao, Yanfang; Li, Huijuan; Xu, Yizhen; Chen, Xiangfeng (Journal of materials science, 2019)
A 2D Z-scheme BiVO 4 /g-C 3 N 4 photocatalyst was successfully synthesized by a two-step hydrothermal/calcination method for overall water splitting. Morphology design to restrain the growth of BiVO 4 nanoplates with thickness around 20 nm was achieved by adjusting the pH value and introducing graphene sheets. Then, the BiVO 4 /g-C 3 N 4 (BVO-CN) hybrid photocatalysts were fabricated with different mass ratios of two components. The structures and optical properties of the BVO-CN photocatalysts were characterized by transmission electron microscope, scanning electron microscope, X-ray diffraction, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy, and photoluminescence spectroscopy. In application, the BVO-CN photocatalysts exhibited the catalytic overall water splitting activity up to 15.6 μmol h −1 for H 2 production and 7.3 μmol h −1 for O 2 evolution under visible light irradiation. A possible Z-scheme mechanism is proposed for the enhanced photocatalytic activity and was further confirmed by electron spin resonance spectroscopy. This study demonstrated enhanced overall water splitting photocatalytic performance of BiVO 4 /g-C 3 N 4 photocatalyst by constructing a 2D nanoplates morphology and shed light on the morphology design of Z-scheme semiconductor materials.